Pengaruh Kualitas Sumber Daya Manusia, Tingkat Pendidikan, Dan Motivasi Terhadap Kinerja Di Sekretariat DPRD - Lilanita, Masrurin; Arisyahidin, Arisyahidin (Otonomi, 2026)
This study investigates the influence of human resource quality, education level, and work motivation on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of Kediri Regency. The research employs a quantitative descriptive-explanatory approach using multiple linear regression analysis with a sample of 60 respondents. Data were collected through questionnaires, interviews, and literature reviews. The findings reveal that human resource quality, education level, and motivation simultaneously exert a significant positive effect on employee performance. Partially, each of the three independent variables also demonstrates a significant impact, with human resource quality being the most dominant factor. The coefficient of determination (R²) of 0.569 indicates that 56.9% of performance variation is explained by the three variables, while the remaining 43.1% is influenced by other factors such as leadership, organizational culture, and external conditions. The study concludes that improving human resource competence, enhancing educational qualifications, and fostering intrinsic motivation are essential strategies for optimizing public sector performance. These findings support the Resource-Based View theory, emphasizing human capital as a strategic asset that drives organizational excellence in public institutions.